VD_FINDINFO HC / 2014 / 541 vom 9. Juli 2014 - VD Tribunal cantonal (2014)
OBLIGATION D'ENTRETIEN, DIVORCE, MESURE PROVISIONNELLE, DROIT ÉTRANGER, FRANCE, CONJOINT | 16 LDIP, 49 LDIP, 61 al. 1 LDIP, 61 al. 2 LDIP, 62 al. 2 LDIP, 62 al. 3 LDIP, 208 al. 1 CC-Français, 212 CC-Français, 214 CC-Français, 4 CLaH 1973, 8 CLaH 1973